EFFECTS OF BURNOUT ON THE SOCIO-PROFESSIONAL ACTIVITY OF TEACHERS - CĂLIN, Mariana Floricica; SEUCEA, Antonia (International Journal of Legal and Social Order, 2022)
Many teachers start their careers with a high level of energy and motivation, wanting to make their subject interesting to their students and demonstrate interest in them. However, professional disillusionment, accompanied by fear, insecurity and anxiety, replaces the joy of teaching. Teacher burnout is a multidimensional construction with three related constructions: emotional exhaustion, depersonalization, and diminishing personal achievement.